PERFORMANCE OF EMPLOYEES AND IMPACT ON PROMOTION OF POSITION - Sarboini Sarboini (Jurnal Ilmiah Peuradeun, 2016)
Performance appraisal is an activity controlling the management of a company. This study is an empirical study that aims to determine the effect of performance appraisal and promotion of their work motivation and their impact on employee performance at Serambi Mekkah University. The research was conducted at Serambi Mekkah University. The populations in this study were all employees at Serambi Mekkah University which amounts to 105 people. Data was collected by distributing questionnaires. Primary data were analyzed with path analysis with the aid of SPSS software. The results showed that, performance appraisal and significant positive effect on work motivation. Performance appraisal and promotion of positive and significant effect on the performance of employees at Serambi Mekkah University. In addition, work motivation can enhance the role of employees in Serambi Mekkah University.